study the effect of alcoholic and watery extracts of garlic and onion plants on growth of candida albicans and Cryptococcus neoformans in vitro&vivo - A., Abd-Alshaheed D. (The Iraqi Journal of Veterinary Medicine, 2008)
This research included study the effect of garlic and onion plantsextracts(alcoholic and watery) in vitro in three different concentrations15%,25%,35% and in vivo in experimental white mice .Research wasperformed by three experiments, first one was conducted to studyeffectiveness of different concentration of alcoholic and watery garlicextract on growth of candida albicans and Cryptococcus neoformans invitro, showed that the effect of alcoholic extract on the growth of candidaalbicans was inhibitory,started from 0.4 mm to 0.1 mm compared withcontrol plats 4.2 mm ,where as the results of the effect on the growth ofCryptococcus neoformans showed more clearness and the inhibitionstarted from 0.6 to inhibit all the growth in plat in comparison withcontrol plats1.4 mm. While the effect of watery garlic extract showed lesseffect and the inhibition began from 0.5 mm to 0.2 mm for candidaalbicans , but the growth inhibition of Cryptococcus neoformans beganfrom 0.4 to 0.15 mm.The second experiment was the same as the firstexperiment , but using alcoholic and extracts onion , the growth ofcandida albicans inhibited by alcoholic exract from 0.6 mm to no growthin the plat , but the inhibition of Cryptococcus neoformans was startedfrom 0.5mm to 0.2 mm for alcoholic onion extract. While the wateryonion extract effect on the growth of candida albicans the inhibitionstarted from 1.6 mm to 1 mm ,but the inhibition of Cryptococcusneoformans was began from 1 mm to 0.3 mm.Third experiment was study the effect of crude garlic and onion alcoholicextract ointment 1% on experimental infection in mice , using 30experimental mice divided to 6 equal groups,each group include 5 mice*groups which infected with candida albicans treated :The group 1,2,3,expermrutly infected with candida albicans ,where asgroup 3,4,6 were infected with Cryptococcus neoformans for 1,2,3 group,treted with the ointment of alcoholic extract of garlic, group 2 treatedwith alcoholic extract ointment of onion, where as group 3 left with notreatment as a control group